2001
DOI: 10.1523/jneurosci.21-10-03674.2001
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Kindling and Neuronal Connections of the Anterior Claustrum

Abstract: The claustrum has been implicated in the kindling of generalized seizures from limbic sites. We examined the susceptibility of the anterior claustrum itself to kindling and correlated this with an anatomical investigation of its afferent and efferent connections.Electrical stimulation of the anterior claustrum resulted in a pattern of rapid kindling with two distinct phases. Early kindling involved extremely rapid progression to bilaterally generalized seizures of short duration. With repeated daily kindling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
74
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 94 publications
13
74
0
Order By: Relevance
“…These included inputs from the anterior claustrum (very dense), secondary motor cortex, AC, TTd, reticular and paraventricular nuclei of thalamus, SNr, IP, and LDT. Previous reports have similarly shown that SMT is strongly reciprocally connected with the anterior claustrum (Yoshida et al, 1992;Zhang et al, 2001).…”
Section: Comparisons Of Projections To Re With Projections To Adjacenmentioning
confidence: 59%
“…These included inputs from the anterior claustrum (very dense), secondary motor cortex, AC, TTd, reticular and paraventricular nuclei of thalamus, SNr, IP, and LDT. Previous reports have similarly shown that SMT is strongly reciprocally connected with the anterior claustrum (Yoshida et al, 1992;Zhang et al, 2001).…”
Section: Comparisons Of Projections To Re With Projections To Adjacenmentioning
confidence: 59%
“…The experiments of Remedios et al (2010), however, show that there is a rapid functional connection between the auditory system and the claustrum. Moreover, Zhang et al (2001), using a similar technique, were able to demonstrate bidirectional connections between the claustrum, on the one hand, and both primary and secondary visual, somatosensory, and auditory cortices on the other.…”
Section: Introductionmentioning
confidence: 89%
“…As well recognized, the CLA is reciprocally linked to virtually all areas of the cortex, including mPFC (Markowitsch et al 1984;Sloniewski et al 1986;Sherk 1988;Witter et al 1988;Kowianski et al 1998;Majak et al 2000;Zhang et al 2001). Using anterograde tracers, Zhang et al (2001) showed that CLA mainly targets AGm of the mPFC. Consistent with this, retrograde injections in the dorsal mPFC were shown to produce dense cell labeling in CLA (Hur and Zaborszky 2005).…”
Section: Other Inputs To Agmmentioning
confidence: 95%